Assessment of Demographic Variables on Mental Illness in Malaysia - Khairul Amri Kamarudin, Mohd; Ekhwan Toriman, Mohd; Abdullah, Nursabrina; Atikah Md Shariff, Nur; Ain Shalilie Shari, Nurul; Nazwa Qanitah Isa, Nurul; Nadhirah Mohd Ramli, Fatin; Nor Fazillah Abdullah, Siti; Saad, Hafiz; Safaniza Che Ani, Nurul (International Journal of Engineering and Technology, 2018)
One of the growing mental illnesses experienced in Malaysia is depression. There was once when one stage was among Malaysians at a critical and higher stage until the attempt to commit suicide. This study has observed a survey conducted by the Ministry of Health Malaysia to identify and understand the vulnerability experienced by every state in Malaysia focuses on the effect of demographic on mental patients by state, age, ethnicity and gender. The data was collected from the Malaysian Health and Morbidity Survey. The findings showed that the highest state of mental illness was the state of Selangor. The overall depression of Malaysians was increasing at an all-time high. The action taken by the Ministry of Health to address mental illness is by using a positive action plan instead of negative. In conclusion, depression at the highest level is one of the first causes of Malaysians to experience mental disorders in every state. This study suggested some proposals as follow-up action at the end of this study.Â